Concerns from bench and insights from bedside: the puzzle of Roxadustat in cancer patients with chemotherapy-induced anemia - Chen, Lin; Liao, Shigen; Jing, Dan; Mao, Linxiu; Tan, Jing (Frontiers in Pharmacology, 2025)
Roxadustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI), is indicated for the treatment of renal anemia. Its therapeutic mechanism involves stabilizing hypoxia-inducible factor-α (HIF-α), thereby stimulating erythropoietin production and regulating iron metabolism. Recent clinical studies have demonstrated that Roxadustat exhibits efficacy comparable to that of erythropoiesis-stimulating agents (ESAs) in the management of chemotherapy-induced anemia (CIA). However, preclinical studies demonstrate HIF-1α activation promotes tumor progression via multiple pathways (metabolic reprogramming, angiogenesis, metastasis, apoptosis resistance, immune evasion, chemoresistance). Current evidence shows no increased malignancy risk with Roxadustat in renal patients. However, while tumor progression events were reported as treatment-emergent serious adverse events (TESAEs) in CIA studies, clinical data linking Roxadustat to tumor progression remain limited. Furthermore, the observation periods in these studies have been short. A causal relationship remains unestablished due to the insufficient duration of observation required to adequately assess potential HIF-driven oncogenic risks. Consequently, Roxadustat poses a clinical dilemma: its efficacy in CIA offers a promising ESAs alternative, but its HIF-driven oncogenic potential necessitates long-term safety assessment in cancer patients. Future studies must prioritize longitudinal monitoring to define the benefit-risk profile.